Analysis of leaf cellulose gayam (inocarpus vagiver) based on different altitudes - Adelheid Adonia Erubun; Ine Arini; Alwi Smith (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Gayam (Inocarpus vagiver) contains natural chemicals in the form of primary metabolites that play an important role in plant survival. The primary metabolites are directly involved in the growth of the Gayam plant. Cellulose is the main component of plant cell walls .Cellulose is a natural material that can be renewed and its uses are very broad. This is because cellulose is widely used for the manufacture of paper and products with various properties. The purpose of this study was to determine the cellulose content of the leaves of the Gayam plant based on different altitudes. The method used in this research is descriptive quantitative and qualitative with the sampling technique using purposive sampling. Based on the iodine test, Gayam leaves in Ema vilage and Airlouw both have cellulose compounds. The average cellulose content in Ema vilage is 0.23315% while Airlouw is 0.20008% which means the higher cellulose content is in Ema.